Inculcating traditional values in the design of healthcare facilities for sustainability: a Malaysian scenario - Mohd Nawawi, Norwina (2007)
Words of wisdoms from our forefathers were based on experience and practicality. Human behaviour and inculcated culture do not change but get adapted in the circumstances. Sustainability is about coming to terms with conflicting presentation in our facility design and the need to change our paradigm of preconception to sincere evaluation of our real day-to- day users’ needs. This paper studies usage of spaces to needs in selected hospitals in Malaysia. The objective is to gather traces of adaptation and innovation by users in their daily routine in hospital environment to sustain operation for patient care in respective locality. Literature review and post occupancy evaluation based on the period from 1997 to date were used for this study. The findings should provide a retrospect on how design decisions were done and imperative for planners and designers (1) to use them as basis for decision making in future hospital projects; and (2) to engage in further research for more practical and customized planning and design solutions for contextual sustainability in the future.